Risky Sexual Behavior in Adolescents - Tahriani, Ridha; Pratiwi, Baiq Bunga Citra; Pujiarohman, Pujiarohman (Jurnal Biologi Tropis, 2025)
Adolescence is a transitional period characterized by physical, mental, and social changes that often encourage risk taking behaviors, including sexual activity. According to the World Health Organization (WHO), adolescents are individuals aged 10–19 years. In Nusa Tenggara Barat (NTB), the prevalence of early marriage reaches 58.1%, which is higher than the national average of 34.0%, and there is a growing trend of premarital sexual activity. These behaviors can lead to unintended pregnancies, abortions, sexually transmitted infections (STIs), and psychosocial problems. This study aims to describe the phenomenon of risky sexual behavior among adolescents in NTB, identify the contributing factors, and discuss its impacts and possible preventive strategies. This research employed a literature review method by collecting, reviewing, and synthesizing scientific articles and relevant reports. The findings indicate that risky sexual behavior is influenced by parenting style, peer pressure, pornography exposure, personality traits, and limited knowledge of sexual and reproductive health, resulting in early marriage, unintended pregnancies, abortions, and an increased risk of STIs and HIV/AIDS. In conclusion, risky sexual behavior among adolescents in NTB remains a significant public health concern. Strengthening comprehensive sexual education, enhancing parental communication, and expanding access to youth friendly reproductive health services are recommended to reduce its prevalence and negative impacts.